Superoscillatory quartz lens with effective numerical aperture greater than one - Yuan, Guanghui (2020)
We report super-resolution high-numerical-aperture and long-working-distance superoscillatory quartz lenses for focusing and imaging applications. At the wavelength of λ = 633 nm, the lenses have an effective numerical aperture of 1.25, a working distance of 200 μm, and a focus into a hotspot of 0.4λ. Confocal imaging with resolution determined by the superoscillatory hotspot size is experimentally demonstrated.